Establishment and multi drug resistance evolution of ST235 Pseudomonas aeruginosa strains in the intensive care unit of a Colombian hospital (2014)
Drug resistant Pseudomonas aeruginosa represents a therapeutic challenge. To assess the diversity of P. aeruginosa antibiotic resistant variants, isolates were recovered from hospital patients in Colombia. Thirty of 60 isolates contained class 1 integrons and five were of Sequence Type ST235 having appeared in a single intensive care unit. All five possessed an unusual integron but showed differences in gene cassette content and the presence/absence of insertion sequence IS26. This showed that differences can arise rapidly, even within a single ICU. Also, the emergence of IS26 in P. aeruginosa is contributing to the evolution of resistance in this bacterium.